IMPLEMENTASI MODEL PEMBELAJARAN GRAPHIC ORGANIZER DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK MTS KHOZINATUL ULUM BLORA - Muhammad Jaelani; Muhammad Nabil; Muhammad Zainal Abidin (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Islamic Cultural History (SKI) learning in Madrasah Tsanawiyah still faces the problem of students’ low learning interest due to monotonous teaching methods that tend to emphasize memorization. This study aims to describe the implementation of a digital-based Graphic Organizer learning model, identify its supporting and inhibiting factors, and analyze the results of its implementation in increasing eighth-grade students’ learning interest at MTs Khozinatul Ulum Blora. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, questionnaires, and documentation. The data were analyzed using descriptive qualitative techniques through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the digital-based Graphic Organizer model was able to improve students’ learning interest, as reflected in increased attention, enthusiasm, activeness, enjoyment, learning motivation, and better understanding of SKI material. Supporting factors included the availability of facilities and infrastructure, teachers’ competence and creativity, and the suitability of SKI material for visual presentation. Meanwhile, inhibiting factors consisted of limited instructional time and technical constraints in using digital media. Therefore, it can be concluded that the digital-based Graphic Organizer learning model is effective as an innovative learning alternative to enhance students’ learning interest in Islamic Cultural History. ABSTRAK Pembelajaran Sejarah Kebudayaan Islam (SKI) di Madrasah Tsanawiyah masih menghadapi permasalahan rendahnya minat belajar siswa akibat metode pembelajaran yang monoton dan berorientasi pada hafalan. Penelitian ini bertujuan untuk mendeskripsikan implementasi model pembelajaran Graphic Organizer berbasis digital, mengetahui faktor pendukung dan penghambatnya, serta menganalisis hasil implementasi model tersebut dalam meningkatkan minat belajar siswa kelas VIII MTs Khozinatul Ulum Blora. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan (field research). Teknik pengumpulan data dilakukan melalui observasi, wawancara, angket, dan dokumentasi. Analisis data dilakukan secara deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan Graphic Organizer berbasis digital mampu meningkatkan minat belajar siswa yang ditandai dengan meningkatnya perhatian, antusiasme, keaktifan, rasa senang, motivasi, serta pemahaman siswa terhadap materi SKI. Faktor pendukung dalam implementasi model ini meliputi ketersediaan sarana prasarana, kompetensi dan kreativitas guru, serta kesesuaian materi SKI dengan penyajian visual. Adapun faktor penghambatnya yaitu keterbatasan waktu pembelajaran dan kendala teknis penggunaan media digital. Dengan demikian, model pembelajaran Graphic Organizer berbasis digital efektif digunakan sebagai alternatif pembelajaran inovatif untuk meningkatkan minat belajar siswa pada mata pelajaran SKI.